Sanctity and mysticism in medieval Egypt : the Wafāʼ Sufi order and the legacy of Ibn ʻArabī - McGregor, Richard J. A. (SUNY series in Islam., 2004)
"Using the original writings of two Egyptian Sufis, Muhammad Wafa' and his son 'Ali, this book shows how the Islamic idea of sainthood developed in the medieval period. Although without a church to canonize its "saints," the Islamic tradition nevertheless debated and developed a variety of ideas concerning miracles, sanctity, saintly intermediaries, and pious role models. In the writings of the Wafa's, a complete mystical worldview unfolds, one with a distinct doctrine of sainthood and a novel understanding of the apocalypse. Using almost entirely unedited manuscript sources, author Richard J.A. McGregor shows in detail how Muhammad and 'Ali Wafa' drew on earlier philosophical and gnostic currents to construct their own mystical theories and notes their debt to the Sufi order of the Shadhiliyya, the mystic al-Tirmidhi, and the great Sufi thinker Ibn 'Arabi. Notably, although located firmly within the Sunni tradition, the Wafa's felt free to draw on Shi'ite ideas for the construction of their own theory of the final great saint."--Jacket.